THE DEVELOPMENT OF LEARNING MEDIA BASED ON MULTILEVEL INTERACTIVE QUIZ FOR EXERCISING AL-QURâAN LETTER READING ON STUDENTS WITH HEARING IMPAIRMENT - Walidah, Isna; Efendi, Mohammad (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
Students with hearing impairment who donât have experience in listening Qurâan have problem in pronouncing the letters of the Qurâan. So, the teacher find difficulties to determine the level of students understanding in reading the letters of Qurâan. The purposes of the research and development was to produce learning media based on multilevel interactive quiz for exercising Al-Qurâan letter reading for students with hearing impairment of grade X. The model in this study refers to Research and Development (R & D) of Borg and Gall. The results of the research was qualified product that can be used by student with hearing impairment. Further research should develop an interactive quiz with emphasis on the diversity of the population and research.Â Siswa tunarungu yang tidak memiliki pengalaman dalam mendengarkan bunyi ayat-ayat Al-Qurâan mengalami hambatan dalam mengucapkan huruf-huruf Al-Qurâan. Hal tersebut menyebabkan pengajar kesulitan untuk mengetahui tingkat pemahaman siswa dalam membaca huruf Al-Qurâan. Penelitian dan pengembangan ini bertujuan untuk menghasilkan media pembelajaran berbasis kuis interaktif bertingkat untuk latihan membaca huruf Al-Qurâan siswa tunarungu kelas X. Model pengembangan dalam penelitian ini mengacu pada model pengembangan Research and Development (R & D) dari Borg dan Gall. Hasil pengembangan adalah produk kuis interaktif bertingkat latihan membaca huruf Al-Qurâan yang telah layak menjadi media pembelajaran siswa tunarungu kelas X. Sebaiknya peneliti selanjutnya mengembangkan kuis interaktif dengan memperbanyak keragaman populasi dan keragaman penelitian.